Analisis Minat Nasabah Pada Perbankan Syariah di Indonesia - Yogi Oriena; Chuzaimah Batubara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to find out the reasons why Islamic banks are less interested than conventional banks. What can affect customer satisfaction. The research was conducted by Meriview 20 international journals. The conclusion of this study regarding customer satisfaction about service quality in Islamic banks. Factors that are the reason people prefer conventional banks compared to Islamic banking.